METODE SYARAH HADIS DALAM KITAB AL-MUNTAQA SYARAH AL-MUWATTA’ - Muhammad Qomarullah (STAI Bumi Silampari, 2020)
Research discusses the methodology of the tradition of hadith in the book of al-Muntaqa which is the syarah al-Muwatta 'which the book was written by Al-Baji, nicknamed by jurists and Mutakallimin, writers, poets as